COMPARISON OF K-AR AGES OF DIAGENETIC ILLITE-SMECTITE TO THE AGE OF A CHEMICAL REMANENT MAGNETIZATION (CRM): AN EXAMPLE FROM THE ISLE OF SKYE, SCOTLAND - Elliott W.C.; Basu A.; Wampler J.M.; Elmore R.D.; Grathoff G.H. (My University, 2006)
The clay fractions of Jurassic marls in the Great Estuarine Group in southern Isle of Skye are composed of mixed-layered illite-smectite (I-S) with large percentages (>85%) of illite layers, kaolinite, and generally smaller amounts of chlorite. These marls have not been buried to the depths normally required to convert smectite to illite-rich I-S, so it is possible that the conversion was in response to heat and hydrothermal fluids from nearby early Tertiary igneous activity ~55 Ma ago. The large percentages of illite layers in I-S, the Środoń intensity ratios, and the Kübler index values appear to be consistent with the formation of diagenetic I-S as a result of relatively brief heating caused by igneous activity. The Jurassic rocks in southern Skye contain a secondary chemical remanent magnetization (CRM) that resides in magnetite and formed at approximately the same time as the Tertiary igneous rocks on Skye. K-Ar age values for I-S based on illite age analysis have been determined to test the hypothesis that the CRM was acquired coincidently with the smectite-to-illite conversion. However, linear extrapolation of K-Ar age vs. percentage of 2M1 polytype (detrital illite) from one marl (EL-6) yields an estimate for the age of diagenetic illite of 106 Ma, which is close to the measured age of the finest subfraction (108 Ma). These estimated and measured age values, however, could be substantially greater than the true age of the diagenetic illite in I-S because of the presence of detrital 1Md illite that was recycled from early Paleozoic shales and whose abundance relative to the diagenetic I-S may have been enhanced because the diagenetic fluid had a low K/Na ratio, limiting the amount of diagenetic illite formed. Nevertheless, most of the illite in the Elgol marls (80% or more in the finest fractions) must be diagenetic and probably formed in response to the early Tertiary magmatism.
Keywords: ILLITE; ISLE OF SKYE; K-AR; SCOTLAND; PALEOMAGNETISM; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская